Eksploracyjna analiza polskojęzycznych ofert zatrudnienia specjalistów z zakresu informatyki - Lula, Paweł (Text Mining Analysis of Polish Job Offers for IT Specialists, 2008)
The problem of document clustering is the main topic of the paper. Two approaches to text clustering are studied. The first one is based on the bag-of-words representation. And the second uses a user-defined ontology. The results show that ontology-based approach is more complex than methods based on the bag-of-words representation but it is far superior to them.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 249-255